Combined Effects of Chrysin Supplementation and Exercise Training on Diabetes-Induced Oxidative Stress and Apoptosis in Rat Testicular Tissue - Shiva Cheraghi Abajlou; Asghar Tofighi; Javad Tolouei Azar; Amir Afshin Khaki; Mazdak Razi (International Journal of Fertility and Sterility)
Background: Diabetes mellitus (DM), one of the most pervasive and enduring metabolic diseases, has been demonstratedto adversely impact male fertility. Conversely, both exercise training and Chrysin have been identified aspotential interventions capable of mitigating the deleterious effects of diabetes on spermatogenesis. Thus, the currentstudy aims to explore the individual and combined influences of Chrysin supplementation and running exerciseon oxidative stress and germ cell apoptosis in the testicular tissue of diabetic adult rats.Materials and Methods: In this experimental study, the DM was induced by streptozotocin (STZ,50 mg/kg). Ratswere divided into control (received STZ solvent), DM-sole, Chrysin-sole (50 mg/kg, daily), moderate-intensityrunning exercise training (MIRET-sole, warm-up, 5 minutes at 30% of Smax1 (Maximum speed); Moderate intensityexercise, 60 minutes at 60% of Smax1, and recovery, 5 minutes to 30% of Smax1), DM+Chrysin, DM+MIRET,and DM+MIRET+Chrysin. Following 8 weeks, the histopathological changes (Johnson’s score, epithelial height,and tubular diameter), testicular malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase(GPX), and the mRNA levels of anti-apoptotic gene Bcl-2 and pro-apoptotic gene Bax was analyzed.Results: Chrysin solely and simultaneous with MIRET could remarkably (P=0.001) improve the DM-induced histopathologicaldamages, increase the testicular SOD and GPx levels, and decline the DM-increased MDA content.Moreover, our results showed that Chrysin solely and more simultaneously with MIRET could significantly (P=0.001)decrease the mRNA expression of Bax and improve the Bcl-2 expression and rebalance the Bax/Bcl-2 balance.Conclusion: Our findings showed that co-administration of Chrysin along with MIRET can significantly amelioratethe DM-induced histopathological, and biochemical impairments and reduce the pro-apoptotic impact of DMon testicular tissue.